Influence of surface roughness of thermal barrier coating on the cooling performance of a film-cooled turbine vane - Xiaoyu Song; Feng Liu; Yan Yan; Wen Wang; Yaning Wang; Wei Sun; Jiahuan Cui (Case Studies in Thermal Engineering)
To explore the impact of thermal barrier coating (TBC) surface roughness on the cooling effectiveness of film-cooled turbine vanes, the GE-E3 high pressure turbine vane was used. Utilizing the method of conjugate heat transfer (CHT) and Computational Fluid Dynamics (CFD), we employed the SST k-ω two-equation turbulence model to conduct numerical simulations of the film cooling process. Our analysis delves into the effects of varying roughness levels (0 μm, 0.81 μm, 2 μm and 3 μm) on vane cooling efficiency, TBC performance, and vane heat transfer coefficient. Results indicate a notable enhancement in vane film cooling efficiency, particularly in proximity to the leading edge (LE), owing to the presence of TBC. As TBC surface roughness increases, heat transfer coefficients on the suction side (SS) and pressure side (PS) near the trailing edge (TE) generally rise, diminishing both cooling and TBC effectiveness. However, divergent outcomes emerge near the LE due to the inherent uncertainty in heat transfer predictions. Notably, reducing TBC surface roughness from 3 μm to 0 μm yields an average cooling efficiency increase of 2.45 %, with a maximum improvement of 2.1 %.